An Assessment of Agroforestry Systems in Selected Community-Based Forest Management Areas in Laguna, Philippines (Philippine Journal of Agricultural Economics, 2018)
Agroforestry has been widely accepted as one of the effective approaches in ensuring sustainability in the uplands. In the Philippines, agroforestry, as a forest management strategy, has been promoted by Community Based Forest Management (CBFM) in response to watershed and forest degradation and climate change. The study assessed the agroforestry systems of CBFM sites in Liliw and Sta. Maria, Laguna focusing on the characterization of agroforestry systems; determination of socio-economic and demographic characteristics of farmers, agrobiodiversity and soil physical and chemical properties for formulation of policy recommendations. The agroforestry systems were characterized based on structure. Soil properties and erodibility were determined through soil sampling, direct on-site measurements and laboratory analysis. Results revealed that farmers practiced shelterbelts/windbreaks-cum live trellis system in Liliw and multilayer tree gardens in Sta. Maria. The agrobiodiversity of agroforestry systems in both sites were moderately diverse for members while low diverse for non-members. Agrobiodiversity indices of agroforestry systems for CBFM members and non-members in Liliw are 2.58 and 1.98, respectively while CBFM members and non-members in Sta. Maria are 2.72 and 0.78, respectively. Farms in both sites had low soil bulk density and erosion rates with high organic matter, Nitrogen, Phosphorous, and Potassium contents.  Regardless of the kind of agroforestry system practiced in the CBFM sites, it has been observed that agroforestry is indeed beneficial for both study sites.